Hydrodynamic stability of flow over kramer-type compliant surface - Chan, Rosa Yue Mei. (2011)
Kramer first introduced the study of hydrodynamic stability of flow over a compliant surface after discovering that the dolphin skin had the capability of reducing drag of the flow of a fluid.